Strategi Think-Talk-Write dalam Pembelajaran Menulis untuk Mengembangkan Kreativitas Siswa Sekolah Menengah Pertama - Anita Candra Dewi (FKIP UNSULTRA, 2026)
This study aims to assess the effectiveness of the Think-Talk-Write (TTW) strategy in teaching writing to develop the creativity of junior high school students. The method used was a literature review, analyzing various scientific sources, including national and international journals, books, and research reports relevant to the topic of TTW and writing. The results of the study indicate that the Think-Talk-Write strategy significantly contributes to improving students' writing skills, particularly in the areas of idea development, writing organization, and creative expression. The